Educational Supervision as a Strategic Instrument in the Professional Development of Teachers at SMP Angkasa Margahayu - R. Supyan Sauri; Muhammad Fahri Rizqi; Harry Nugraha; Wawan Rilyawan; Muthi Fadilah (Universitas Pendidikan Mandalika, 2025)
Educational supervision plays a strategic role in improving teacher competence and learning quality, particularly in secondary schools. However, supervision in Indonesia is often administrative and lacks adaptability to institutional dynamics. This study aims to analyze the contribution of supervision to the development of teachers' teaching skills, evaluate effective supervision models, and identify challenges in implementing innovative supervision at SMP Angkasa Margahayu, Indonesia. This study employs a descriptive qualitative approach with data collection techniques, including in-depth interviews, participatory observation, and document analysis. The informants consisted of the school principal and eight active teachers. Data were analyzed thematically using triangulation techniques to enhance the validity of the findings. Collaborative, reflective, and training-based supervision significantly improves teachers' pedagogical skills. An effective supervision model involves peer mentoring, constructive feedback, and technology use. However, teacher resistance, time constraints, limited resources, and external involvement remain major challenges to its implementation. Strategically and contextually designed supervision can serve as a sustainable instrument for teachers’ professional development. Integration of reflective approaches and structural policies is needed to overcome implementation barriers. Keywords: Educational supervision, Strategic Instrument, Profesional Abstrak. Supervisi pendidikan memainkan peran strategis dalam meningkatkan kompetensi guru dan mutu pembelajaran, terutama di sekolah menengah. Namun, pelaksanaan supervisi di Indonesia kerap bersifat administratif dan kurang adaptif terhadap dinamika institusi. Penelitian ini bertujuan untuk menganalisis kontribusi supervisi terhadap pengembangan keterampilan mengajar guru, mengevaluasi model supervisi yang efektif, dan mengidentifikasi tantangan implementasi supervisi inovatif di SMP Angkasa Margahayu. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data melalui wawancara mendalam, observasi partisipatif, dan studi dokumentasi. Informan terdiri dari kepala sekolah dan delapan guru aktif. Data dianalisis secara tematik menggunakan teknik triangulasi untuk meningkatkan validitas temuan. Supervisi yang bersifat kolaboratif, reflektif, dan berbasis pelatihan menunjukkan kontribusi nyata terhadap peningkatan keterampilan pedagogis guru. Model supervisi efektif melibatkan peer mentoring, feedback konstruktif, dan pemanfaatan teknologi. Namun, resistensi guru, keterbatasan waktu, sumber daya, dan keterlibatan eksternal masih menjadi tantangan besar dalam pelaksanaannya. Supervisi yang dirancang secara strategis dan kontekstual mampu menjadi instrumen pembinaan profesional guru yang berkelanjutan. Diperlukan integrasi antara pendekatan reflektif dan kebijakan struktural untuk mengatasi hambatan implementasi. Kata kunci: Supervisi pendidikan; Instrumen Strategi, Profesional.